An experimental validation method of wind tunnel measurements on FIFA approved footballs using kicking tests in wind-free conditions - Rogers, D.; Passmore, M.; Harland, A.; Jones, R.; Holmes, C.; Lucas, T. (Procedia Engineering, 2010)
This study sought to determine the in-flight performance of footballs in a wind free environment to validate against simulated flight performance based on measured wind tunnel data. A mechanical kicker was used to provide consistent kicking parameters capturing flight trajectories using High Speed Video and a radar tracking system. Simulated trajectories using the same initial conditions were generated using aerodynamic drag and lateral force data acquired in a low speed wind tunnel. The results demonstrate that the ball performance ranking based on RMS deviation in-flight is the same for the real kicks and that predicted from the wind tunnel tests.